Evaluation of Nutritional Composition of Small Ruminants’ Feed stuffs widely grown in Khulna Region of Bangladesh: Evaluation of feed stuff - Rumpa, Sazia Parvin; Islam, Sarder Safiqul; Islam, Md Shafiqul; Sun, Minhazul Abedin (South Asian Journal of Agriculture, 2023)
Feed stuffs availability is one of the extreme obstacles to small ruminant production, particularly during the dry season. In Khulna region, there are several feed stuffs, fodders, grasses and weeds, but their potential has not yet been completely realized due to a lack of understanding of their nutritional value. Therefore, the research was carried out to determine the nutritional value of available feed stuffs for small ruminants in the Khulna region. Roughage and concentrate samples were collected from different areas of Khulna region. All of the samples were taken in triplicates and analyzed accordingly. The results revealed that among the grass species, the Gitlacontains the highestamount of DM content (39.74%)and lowest in Kalmilata (13.90%). The crude protein contents in grass species ranged from 6.5% to 25.65% being highest in Helencha and lowest in Para. Highest EE content was found in German lata (7.05%), followed by Kakpaya (6.72%). The CF content varied between 9.39% in Chanchito 40.05%in Para. Kakpayacontains the highest ash (17.45%), while Pakchong the lowest (8.68%).Mustard oil cake containsthe highestamount of DM (94.77%) among the concentrates, whereas red wheat contains the lowest (89.85%). Crude protein (CP) contents of concentrate feed stuffs ranged from 5.35% in gram bran to 50.75% in soybean meal. Rice polish (21.12%) showed the highest EE concentration and it was lowest in motor bran (2.50%). The maximum concentration of CF was found in Khesari bran (27.17%), while the lowest was in maize (1.82%). It could be concluded that evaluated concentrate feeds and grass species could serve as prospective livestock feeds in southwest Bangladesh. South Asian J. Agric., Vol. 9, No.1&2, 2022-‘23: 31-38